Tendencies of coal industry development in Ukraine - Snihur, V.; Malashkevych, D.; Vvedenska, T. (Розробка родовищ, 2016)
Purpose. Analysis of the current state and prospects of Ukraine coal industry development until 2020. Methods. Complex analysis of data regarding mine productivity, coal reserves, mine funds as well as coal consump-tion and electricity generation has been presented in the paper. The studies of statistics related to geological and extraction thickness in longwall faces are discussed. Findings. The current state of Ukraine coal mining industry and prospects of its development for the period until 2020 are considered. The analysis of Ukraine mine fund conditions is carried out. Statistical data of gross coal pro-duction at state-maintained and private mines are given. The reasons for low profitability and coal production decline in the country are considered. Results of the research into ash content of extracted coal, formation and accumulation of mine waste are interpreted. The main promising trends of efficient energy resources use and reduction of environ-mental impact on coal-mining regions are emphasized. Цель. Анализ современного состояния и перспектив развития угледобывающей промышленности Украины до 2020 года. Методика. Для достижения цели использован комплексный анализ данных производственной мощности угольных предприятий, шахтных фондов, а также потребления угля и производства электроэнергии. Представ-лены исследования статистических данных геологической и вынимаемой мощности в очистных забоях. Результаты. В статье проведен анализ текущего состояния угольной промышленности Украины и пред-ставлены перспективы ее развития до 2020 года. Проведен анализ состояния шахтного фонда Украины. Пред-ставлены статистические данные добычи угля предприятиями государственной и негосударственной форм собственности. Рассмотрены причины низкой рентабельности добычи угля в стране. Представлены результаты исследований зольности добываемого угля, образования и накопления отходов горнодобывающих предприя-тий. Выделены основные приоритетные направления эффективного использования энергоресурсов и снижения экологической нагрузки на угледобывающие регионы. Мета. Аналіз сучасного стану та перспектив розвитку вугледобувної галузі України до 2020 року. Методика. Для досягнення мети використано комплексний аналіз даних виробничої потужності вугільних підприємств, запасів вугілля, шахтних фондів, а також споживання вугілля та вироблення електроенергії. Пред-ставлені дослідження статистичних даних геологічної та виймальної потужності в очисних вибоях. Результаты. У статті проведено аналіз поточного стану вугільної промисловості України та представлені перспективи її розвитку до 2020 року. Проведено аналіз стану шахтного фонду України. Наведені статистичні данні видобутку вугілля підприємствами державних і недержаних форм власності. Розглянуто причини низької рентабельності видобутку вугілля у країні. Представлені результати досліджень зольності вугілля, утворення та накопичення відходів гірничодобувних підприємств. Виділені основні пріоритетні напрямки ефективного вико-ристання енергоресурсів і зниження екологічного впливу на вуглевидобувні регіони.